Laringoespasmo en anestesia pediátrica con el uso de la máscara laríngea vs tubo endotraqueal: Ensayo clínico de no inferioridad (2018)
ABSTRACT: Introduction: Airway-related problems are the most common perioperative complications in pediatric anesthesia and, among them, the most significant is laryngospasm. The type of device used to secure the airway has been found to be among the factors responsible for this outcome. Objective: To determine whether the use of the classic laryngeal mask (LM) creates a non-inferior risk of laryngospasm compared with the use of the endotracheal tube (ET) in children. Method: Non-inferiority, controlled, double-blind clinical trial with random assignment that included 260 children ages 2 to 14 years, American Society of Anaesthesiology I to III, taken to surgical procedures under general anesthesia. The primary outcome was the development of laryngospasm, and the need to exchange devices, airway trauma, and other respiratory complications were assessed as secondary outcomes. A 10% non-inferiority margin was selected for the difference between the 2 devices. Results: A total of 270 patients were recruited, and 135 were assigned to each group. Laryngospasm occurred in 3.3% of the patients, with an incidence of 5.2% in the LM group versus 1.5% for the ET group, for a difference of 3.7% and a 95% confidence interval (-0.7%, 7.9%). No differences were found among bradycardia, cardiac arrest, and death outcomes. Conclusion: The use of LM in children 2 to 14 years of age taken to various surgical procedures is not inferior or superior to ET in terms of the development of laryngospasm.